Transactions on Engineering Technologies 25th World Congress on Engineering (WCE 2017) - Ao, Sio-Iong.; Gelman, Len.; Kim, Haeng Kon.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume contains a selection of revised and extended research articles written by prominent researchers participating in a large international conference on Advances in Engineering Technologies and Physical Science which was held in London, UK, 5-7 July, 2017. Topics covered include mechanical engineering, engineering mathematics, computer science, knowledge engineering, electrical engineering, wireless networks, and industrial applications. With contributions carefully chosen to represent the most cutting-edge research presented during the conference, the book offers the state of art in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.
1. Homogenization of Electromagnetic Fields Propagation in a Composite -- 2. Statistics of Critical Load in Arrays of Nanopillars on Nonrigid Substrates -- 3.Quantifying the Impact of External Shocks on Systemic Risks for Russian Companies Using Risk Measure DCoVaR -- 4. AN INNOVATIVE DSS FOR THE CONTINGENCY RESERVE ESTIMATION IN STOCHASTIC REGIME -- 5. A Simulation Study on Indoor Location Estimation Based on the Extreme Radial Weibull Distribution -- 6. Infant Mortality and Income per Capita of World Countries for 1998-2016: Analysis of Data and Modeling by Increasing Returns -- 7. Mathematical Models for the Study of Resource Systems Based on Functional Operators with Shift -- 8. A USEFUL EXTENSION OF THE INVERSE EXPONENTIAL DISTRIBUTION -- 9. ON COMPUTING THE INVERSE OF VANDERMONDE MATRIX VIA SYNTHETIC DIVISIONS -- 10. Application and generation of the univariate Skew Normal random variable -- 11. Semi-Analytical Methods For Higher Order Boundary Value Problems -- 12. DEVELOPING INDONESIAN HIGHWAY CAPACITY MANUAL BASED ON MICROSIMULATION MODEL (A CASE OF URBAN ROADS) -- 13. NATURAL FREQUENCIES OF AN EULER-BERNOULLI BEAM WITH SPECIAL ATTENTION TO THE HIGHER MODES VIA VARIATIONAL ITERATION METHOD -- 14. LEARNING NOISE IN WEB DATA PRIOR TO ELIMINATION -- 15. LEVERAGING LEXICON-BASED SEMANTIC ANALYSIS TO AUTOMATE THE RECRUITEMENT PROCESS -- 16. THE Universal Personalized Approach for Human Knowledge Processing -- 17. The Use of Scalability of Calculations to Engineering Simulation of Solidification -- 18. Vision-based collision avoidance for Service Robot -- 19. IDENTITY AND ENTERPRISE LEVEL SECURITY -- 20. COMPREHENSIVE STUDY FOR A RAIL POWER CONDITIONER BASED ON A SINGLE-PHASE FULL-BRIDGE BACK-TO-BACK INDIRECT MODULAR MULTILEVEL CONVERTER -- 21. JITTER AND PHASE-NOISE IN HIGH SPEED FREQUENCY SYNTHESIZER USING PLL -- 22. Detection of Winding (Shorted-Turn) Fault in Induction Machine at Incipient Stage using DC-Centered Periodogram -- 23. AN INTRA-VEHICULAR WIRELESS SENSOR NETWORK BASED ON ANDROID MOBILE DEVICES AND BLUETOOTH LOW ENERGY -- 24. EXTENDED PERFORMANCE RESEARCH ON 5 GHZ IEEE 802.11 N WPA2 LABORATORY LINKS -- 25. MEMBRANE AND RESINS PERMEATION FOR LACTIC ACID FEED CONVERSION ANALYSIS -- 26. DNA SEQUENCES CLASSIFICATION USING DATA ANALYSIS -- 27. MANAGING INVENTORY ON BLOOD SUPPLY CHAIN -- 28. Pore-Scale Modeling of Non-Newtonian Fluid Flow through Micro-CT Images of Rocks -- 29. STUDY OF FRICTION MODEL EFFECT ON A SKEW HOT ROLLING NUMERICAL ANALYSIS -- 30. RESIDUAL STRESS SIMULATIONS OF GIRTH WELDING IN SUBSEA PIPELINES.
Keywords: Computational intelligence; Data mining; Control engineering; Robotics; Automation; Bioinformatics; Computational Intelligence; Data Mining and Knowledge Discovery; Control and Systems Theory; Control, Robotics, Automation; Computational and Systems Biology